Understanding vegetable farmers' adoption, dis-adoption, and non-adoption decisions of pest management by pheromone trapping. - Muhammad Humayun Kabir; Sk Md Nur-E-Alam; Avishek Datta; Mou Leong Tan; Md Sadique Rahman (PLoS ONE, 2023)
The use of pheromone traps can minimize the excess application of synthetic insecticides, while can also benefit the environment. The use of pheromone traps has been promoted and suggested to vegetable farmers of Bangladesh for widespread adoption. However, the majority of farmers have continued to spray insecticides instead of using pheromone traps. The present study investigated the factors influencing farmers' adoption, dis-adoption, and non-adoption behavior of pheromone traps for managing insect pests. Primary data were collected from 438 vegetable growers. Data were analyzed using descriptive statistics and multinomial logistic regression. About 27% of the farmers abandoned the technique shortly after it was adopted as it was time-consuming to manage insect pests. Marginal effect analysis revealed that the likelihood of continued adoption was 34.6% higher for farmers who perceived that pheromone traps were useful in controlling insect pests. In contrast, the likelihood of dis-adoption was 16.5% and 10.4% higher for farmers who maintained communication with private pesticide company agents and neighbor farmers, respectively. Extension services by government extension personnel might be encouraged and maintained as a key component in increasing farmer awareness regarding the use of pheromone trap. Strategies to promote pheromone traps in vegetable production should highlight the positive impacts to farmers and the environment, as this would most likely lead to their continued and widespread use after initial adoption.